Independent Prognostic Value of Stroke Volume Index in Patients With Immunoglobulin Light Chain Amyloidosis. (May 2018) - Milani, Paolo; Dispenzieri, Angela; Scott, Christopher G.; Gertz, Morie A.; Perlini, Stefano; Mussinelli, Roberta; Lacy, Martha Q.; Buadi, Francis K.; Kumar, Shaji; Maurer, Mathew S.; Merlini, Giampaolo; Hayman, Suzanne R.; et al.
Abstract : Background: Heart involvement is the most important prognostic determinant in AL amyloidosis patients. Echocardiography is a cornerstone for the diagnosis and provides important prognostic information. Methods and Results: We studied 754 patients with AL amyloidosis who underwent echocardiographic assessment at the Mayo Clinic, including a Doppler-derived measurement of stroke volume (SV) within 30 days of their diagnosis to explore the prognostic role of echocardiographic variables in the context of a well-established soluble cardiac biomarker staging system. Reproducibility of SV, myocardial contraction fraction, and left ventricular strain was assessed in a separate, yet comparable, study cohort of 150 patients from the Pavia Amyloidosis Center. The echocardiographic measures most predictive for overall survival were SV index <33 mL/min, myocardial contraction fraction <34%, and cardiac index <2.4 L/min/m 2 with respective hazard ratios (95% confidence intervals) of 2.95 (2.37–3.66), 2.36 (1.96–2.85), and 2.32 (1.91–2.80). For the subset that had left ventricular strain performed, the prognostic cut point was −14% (hazard ratios, 2.70; 95% confidence intervals, 1.84–3.96). Each parameter was independent of systolic blood pressure, Mayo staging system (NT-proBNP [N-terminal pro-B-type natriuretic peptide] and troponin), and ejection fraction on multivariable analysis. Simple predictive models for survival, including biomarker staging along with SV index or left ventricular strain, were generated. Conclusions: SV index prognostic performance was similar to left ventricular strain in predicting survival in AL amyloidosis, independently of biomarker staging. Because SV index is routinely calculated and widely available, it could serve as the preferred echocardiographic measure to predict outcomes in AL amyloidosis patients. Abstract : Supplemental Digital Content is available in the text.